Anaesthesia for deep brain stimulation. Issue 5 (October 2015) - Grant, Ryan; Gruenbaum, Shaun E.; Gerrard, Jason
<x xml:space="preserve">Abstract</x> Purpose of review Deep brain stimulation (DBS) is a well tolerated and efficacious surgical treatment for movement disorders, chronic pain, psychiatric disorder, and a growing number of neurological disorders. Given that the brain targets are deep and small, accurate electrode placement is commonly accomplished by utilizing frame-based systems. DBS electrode placement is confirmed by microlectrode recordings and macrostimulation to optimize and verify target placement. With a reliance on electrophysiology, proper anaesthetic management is paramount to balance patient comfort without interfering with neurophysiology. Recent findings To achieve optimal pain control, generous amounts of local anaesthesia are instilled into the planned incision. During the opening and closing states, conscious sedation is the prevailing method of anaesthesia. The preferred agents are dexmedetomidine, propofol, and remifentanil, as they affect neurocognitive testing the least, and shorter acting. All the agents are turned off 15–30 min prior to microelectrode recording. Dexmedetomidine has gained popularity in DBS procedures, but has some considerations at higher doses. The addition of ketamine is helpful for pediatric cases. Summary DBS is a robust surgical treatment for a variety of neurological disorders. Appropriate anaesthetic agents that achieve patient comfort without interfering with electrophysiology are paramount.